2022
DOI: 10.1038/s41598-022-11275-9
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus impacts extracellular vesicle composition and cellular gene expression in macaque early gestation trophoblasts

Abstract: Zika virus (ZIKV) infection at the maternal–placental interface is associated with adverse pregnancy outcomes including fetal demise and pregnancy loss. To determine how infection impacts placental trophoblasts, we utilized rhesus macaque trophoblast stem cells (TSC) that can be differentiated into early gestation syncytiotrophoblasts (ST) and extravillous trophoblasts (EVT). TSCs and STs, but not EVTs, were highly permissive to productive infection with ZIKV strain DAK AR 41524. The impact of ZIKV on the cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Total RNA was reverse transcribed using a SuperScript III First-Strand Synthesis SuperMix kit (Invitrogen, Waltham, MA)) following the manufacturer’s recommended protocol and a starting input of 3 μg of total RNA. cDNA was diluted with water 1:5 and RT-qPCR reactions were prepared by combining iQ SYBR green supermix (mBio-Rad, Hercules CA), primers and water as previously described [ 19 ]. The primer sequences were as follows: IFNλ-1 forward 5’-ATCGTGGTGCCTGGTGACT TT-3’ and reverse 5’-TTGAGTGACTCTTCCAAGGCA-3’ and beta-actin forward 5’-CTACCATGAGCTGCGTGTGG-3’ and reverse 5’-GTACCATGGCTGGGGTGTTGA-3’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was reverse transcribed using a SuperScript III First-Strand Synthesis SuperMix kit (Invitrogen, Waltham, MA)) following the manufacturer’s recommended protocol and a starting input of 3 μg of total RNA. cDNA was diluted with water 1:5 and RT-qPCR reactions were prepared by combining iQ SYBR green supermix (mBio-Rad, Hercules CA), primers and water as previously described [ 19 ]. The primer sequences were as follows: IFNλ-1 forward 5’-ATCGTGGTGCCTGGTGACT TT-3’ and reverse 5’-TTGAGTGACTCTTCCAAGGCA-3’ and beta-actin forward 5’-CTACCATGAGCTGCGTGTGG-3’ and reverse 5’-GTACCATGGCTGGGGTGTTGA-3’.…”
Section: Methodsmentioning
confidence: 99%
“…Ex vivo and in vitro studies provide somewhat conflicting results. Some studies show that STBs are resistant to ZIKV infection due to potent type III interferon responses [10,16,17]; however, other studies find that derived and differentiated STBs are susceptible [18][19][20]. This inconsistency may reflect the maturity of the derived STBs, which may be more representative of primitive STBs present during early implantation rather than those present in the more mature placenta [20].…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of Snx5 in PRV-infected sEVs suggest the possible role of secretory autophagy during infection of placental cells. Snx1 was also observed to be differentially upregulated in EVs secreted by ZIKV-inoculated trophoblast cells in a macaque ZIKV infection model of pregnancy ( 16 ). In addition to Snx9, various proteins of the Snx family were detected to be upregulated in ZIKV-infected sEVs, and further analysis of Snx6 and 9 showed that disruption of MDV biogenesis affects ZIKV replication and infectivity, in addition to increasing the amount of cytosolic mtDNA following infection ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, placenta-derived sEVs are key modulators of maternal immune tolerance of the fetus and defense against pathogens during pregnancy, and contribute to immune cell activation, differentiation, and maturation ( 15 ). For example, ZIKV infection of a primate trophoblast cell model, which was representative of the human placenta during the early first trimester, revealed alterations in the protein and microRNA (miRNA) content of EVs secreted upon ZIKV inoculation ( 16 ). These findings demonstrate the importance of placenta-derived sEVs as important communicators at the maternal-fetal interface and their potential as biomarkers of pregnancy complications, including ZIKV-induced birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo and in vitro studies provide somewhat conflicting results. Some studies show that STBs are resistant to infection due to potent type III interferon responses [10,16,17]; however, other studies find that derived and differentiated STBs are susceptible [18][19][20]. This inconsistency may reflect the maturity of the derived STBs, which may be more representative of primitive STBs present during early implantation rather than those present in the more mature placenta [20].…”
Section: Introductionmentioning
confidence: 99%